Toxicological effects of micro/nano-plastics on mouse/rat models: a systematic review and meta-analysis - Liu, Weijia; Zhang, Bowen; Yao, Qianqian; Feng, Xihua; Shen, Tianling; Guo, Peisen; Wang, Panpan; Bai, Yitong; Li, Bo; Wang, Peixi; Li, Ruiling; Qu, Zhi; et al. (Frontiers in Public Health, 2023)
Micro/nano-plastics (MNPs) are considered a heterogeneous class of environmental contaminants that cause multiple toxic effects on biological species. As the commonly used mammalian models to study the effects of MNPs with regard to their toxic effects, the mouse and rat models are making a great contribution to the disciplines of environmental toxicology and medical health. However, the toxic effects of MNPs have not been systematically summarized. Therefore, a systematic review and a meta-analysis of the toxic effects of MNPs on mouse/rat models were conducted. A total of seven main categories were established in this systematic review, and 24 subcategories were further divided according to the specific physiological significance of the endpoint or the classification of the physiological system, which covered all the selected pieces of literature. A total of 1,762 biological endpoints were found, and 52.78% of them were significantly affected. This fact indicates that there are relative factors, including the size, polymer type, concentration, and exposure time of MNPs and different sexes of mouse/rat models that could significantly affect the biological endpoints. These biological endpoints can be classified into various factors, such as the dose–response relationships between MNP concentration and physiological categories of the nervous system, growth, reproduction, digestive tract histopathology, and inflammatory cytokine level, among others. MNPs negatively affected the blood glucose metabolism, lipid metabolism, and reproductive function in mice. The reproductive function in male mice is more sensitive to the toxic effects of MNPs. These findings also provide insights into and directions for exploring the evidence and mechanisms of the toxic effects of MNPs on human health. It is clear that more research is required on the pathological mechanisms at the molecular level and the long-term effects of tissue accumulation.